A retrospective study in coping strategies for stress of students taking physical education classes during the pandemic - Aseneta, Charisse Divine M. 1998-; Callanta, Hercules P. (College of Human Kinetics, University of the Philippines Diliman, 2023)
Stress is a normal reaction to pressures that surpass a person's capacity to cope. When people feel threatened or overburdened, they experience it. This study has been established to determine the coping strategies adopted by college students in physical education classes in dealing with the physical, emotional, and mental stress experienced during the pandemic. Furthermore, the study uses simple random sampling to the 124 college students from a variety of courses in a private school in the Metropolis in Mindanao. The study utilizes the adapted questionnaire to determine the stress coping strategies in terms of physical, emotional, and mental stressors. Moreover, the study used frequency, mean, and standard deviation to better understand response distribution, central tendency, and variability. These assessments assist in analyzing stress coping mechanisms in college students’ physical education. Findings revealed that the PE students’ coping strategies in terms of physical stress give the participants more time to interact with their family and loved ones, and abuse of prohibited drugs, smoking, or alcoholic drinks to manage stress have not manifested. Nevertheless, sleep deprivation or change of sleeping pattern has been noted.
Vita
Thesis (Bachelor of Sports Science) -- University of the Philippines Diliman
Includes bibliographical references
Keywords: Stress (Psychology); COVID-19 Pandemic, 2020.; Stress management; Physical education and training